SZ_GERICHTE STK 2024 37 vom 1. April 2025 , einfache Körperverletzung, evtl. mehrfache Tätlichkeiten, Beschimpfung - SZ Gerichte (2025)
einfache Körperverletzung, evtl. mehrfache Tätlichkeiten, Beschimpfung | Strafgesetzbuch